1997
DOI: 10.4141/a96-105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pure fumonisin B1 on various metabolic parameters and carcass quality of growing-finishing swine — preliminary findings

Abstract: . 1997. Impact of pure fumonisin B 1 on various metabolic parameters and carcass quality of growing-finishing swine -preliminary findings. Can. J. Anim. Sci. 77: 465-470. Mycotoxin fumonisin B 1 (FB 1 ) is a common contaminant of corn and a causative agent of different animal and human diseases. An experiment was conducted to assess the impact of pure FB 1 on carcass quality of growing-finishing swine. Pigs were fed diets containing 0, 0.11, 0.33 and 1.0 mg FB 1 kg -1 (ppm) until market weight. Although perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
0
17
2
Order By: Relevance
“…Motelin et al (1994) reported similar effects on serum enzymes indicative of liver damage and elevated cholesterol when they fed weaned piglets diets with 175 and 101 ppm FB. Rotter et al (1996) and Zomborszky-Kovacs et al (2002) also found increased GOT, but at much lower fumonisin concentrations (10 ppm) than in the present study. Unlike the data of Zomborszky et al (2002), but similar to that of Rotter et al (1996), animals consuming the FB diets had significant decreased ADG and G:F. The addition of the activated carbon was not effective in preventing the decreased performance effects associated with fumonisin consumption.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Motelin et al (1994) reported similar effects on serum enzymes indicative of liver damage and elevated cholesterol when they fed weaned piglets diets with 175 and 101 ppm FB. Rotter et al (1996) and Zomborszky-Kovacs et al (2002) also found increased GOT, but at much lower fumonisin concentrations (10 ppm) than in the present study. Unlike the data of Zomborszky et al (2002), but similar to that of Rotter et al (1996), animals consuming the FB diets had significant decreased ADG and G:F. The addition of the activated carbon was not effective in preventing the decreased performance effects associated with fumonisin consumption.…”
Section: Discussioncontrasting
confidence: 69%
“…Studies on the toxicity of FB in pigs have been done using either purified FB (Haschek et al, 1992;Prelusky et al, 1996;Rotter et al, 1996), cultured material containing FB (Casteel et al, 1993;Colvin et al, 1993;Fazekas et al, 1998;Gumprecht et al, 1998;Smith et al, 1999;Zomborszky et al, 2000;Zomborszky-Kovacs et al, 2002), or with naturally contaminated feeds (Haschek et al, 1992;Motelin et al, 1994). In the present study, consumption of diets containing 30 ppm of FB (from cultured material) decreased ADG and G:F and increased serum activities of the liver enzymes GOT and GGT and cholesterol in postweaned piglets fed for 42 d, but did not significantly affect weights of liver, kidneys, and pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased feed efficiency may be caused by increased oxygen consumption (10,35). Increased variability of carcass quality was reported with ingestion of FB 1 at 1 ppm (44).…”
Section: Overview Of Fumonisin Toxicosismentioning
confidence: 98%
“…Although decreased food consumption often is seen with naturally contaminated corn, presumably due to palatability problems (29,30), observations with FB 1 , either as pure compound or in culture material, have been variable; no effect as well as increased and decreased feed consumption and weight gain have been reported (28,(42)(43)(44). Decreased feed efficiency may be caused by increased oxygen consumption (10,35).…”
Section: Overview Of Fumonisin Toxicosismentioning
confidence: 99%
“…Conversely, health and performance of pigs were also affected at lower fumninsin concentrations in their diet in some studies. Changes in feed consumption and increased variability in carcass characteristics were observed in growing‐finishing swine in the treatment of 1.0 mg pure FB 1 /kg diet (Rotter, Prelusky, Fortin, Miller, & Savard, ). A dose–response study showing how even a very low concentration of fumonisins can affect swine performance reports erratic growth in pigs at the concentration of 0.1 mg purified FB 1 /kg in the diet.…”
Section: Fumonisin Exposure and Growth Impairmentmentioning
confidence: 99%